Education for publishers in Croatia: is it feasible? - Horvat, Aleksandra; Pintarić, Krešimir; Fabris, Martina (2002)
It is well known that following the beginning of the nineties the large state&not ; owned publishing houses were either said to private individuals or went bankrupt. At the same time the publishing industry was taken over by a great number of small publishers. Same of them survived and stayed in business, white same published a few titles and disappeared. The appearance of the electronic books in the market emphasizes the need for education for the publishing industry, because it requires new knowledge and skills in let, as well as knowledge of the copyright and metadata management. Therefore it was decided to conduct a research, which would help identify the needs for training and/or education in the publishing industry.
ENG